Relationship between rat renal accumulation of gentamicin, tobramycin, and netilmicin and their nephrotoxicities. - Brier, M E (1985)
Gentamicin, tobramycin, and netilmicin were given to rats in daily doses of either 5 or 20 mg/kg for 30 days to determine the renal accumulation kinetics of the compounds and to correlate steady-state renal parenchymal concentrations with nephrotoxicity. Four rats from each group were sacrificed daily and renal parenchymal tissue concentrations were determined microbiologically. Nephrotoxicity was assessed by changes in creatinine values in serum, renal creatinine clearances, and pathological scores. There was no indication of aminoglycoside-induced nephrotoxicity in any tests performed. The following steady-state levels resulted: 36, 148, and 176 micrograms/g after 5 mg/kg per day and 148, 260, and 510 micrograms/g after 20 mg/kg per day for tobramycin, gentamicin, and netilmicin, respectively. We conclude that aminoglycoside parenchymal accumulation in rats follows this order: tobramycin less than gentamicin less than netilmicin. Therefore, differences in the relative toxicities of gentamicin, tobramycin, and netilmicin do not correlate with the renal parenchymal accumulation of these agents and may be more dependent on intrinsic toxicity to the renal proximal tubule than to the concentration of the aminoglycoside in the kidney.